THE EFFECT OF MANDATORY EXPENDITURES ON BASIC SERVICES OF THE LOCAL GOVERNMENT ON GROSS PER CAPITA REGIONAL DOMESTIC PRODUCTS IN EAST JAVA PROVINCE - Enrico Adhanur Karyadi; Hasna Imtiyaz Hanifah (Jurnal REP (Riset Ekonomi Pembangunan), 2022)
In Law Number 23 of 2014, government affairs are divided into three categories that are absolute, concurrent, and general government affairs. Decentralization of mandatory government affairs was expected to fulfill the state and local government goals, one of which is increasing welfare measured by income per capita. Government expenditure in mandatory government affairs was utilized to accomplish this. This study examined the effect of education, health, and social security expenditures on the gross regional domestic product (GRDP) per capita. The research sample was regency and city governments in East Java Province from 2014 to 2016. The research method was quantitative research methods. The results showed that education and social security expenditures negatively impacted GRDP per capita, while health expenditure positively impacted GRDP per capita. Local governments should reform the spending policies to ensure the efficiency and effectiveness of the budget used. The central government, authorities, and the public should also adequately monitor the local government.